Deposits in the lungs of Kwädąy Dän Ts'ìnchį man: Characterization by a combination of analytical microscopical methods. Issue 2 (29th August 2018) - Monsalve, M. Victoria; Humphrey, Elaine; Yueyang, Shen; Schulze, H. Georg; Atkins, Chad G.; Blades, Michael W.; Konorov, Stanislav O.; Turner, Robin F. B.; Walker, David C.
Abstract: Objectives: The approximately 250 years old remains of the Kwädąy Dän Ts'ìnchį man were found in a glacier in Canada. Studying the state of preservation of the corpse, we observed black deposits in his lung. Following this observation we wanted to determine: (1) location of the deposits in the lung tissue, (2) composition and origins of the deposits. Methods: By light microscopy (LM) and transmission electron microscopy (TEM), we studied the deposits in the Kwädąy Dän Ts'ìnchį man' s lung and compared it with distribution of anthracotic deposits in contemporary samples from the David Harwick Pathology Centre (DHPC). To determine chemical composition of the inclusions we used Raman spectroscopy. Scanning electron microscopy and elemental mapping was used for determine the chemical elements. Results: The histopathological identification of anthracosis in the Kwädąy Dän Ts'ìnchį man's lung allowed us to distinguish crushed parenchyma from conducting airway tissue and identification of particles using LM and TEM. Crystal particles were found using TEM. Ordered carbonaceous material (graphene and graphite), disordered carbonaceous material (soot) and what might be minerals (likely conglomerates) were found with Raman spectrometry. Gold and lead particles in the lung were discovered with scanning electron microscopy and elemental mapping. Conclusions: Presence of soot particles in anthracotic areas in the Kwädąy Dän Ts'ìnchį man's lung probably were due to an inhalation of particles in open fires. Gold and lead particles are most likely of an environmental origin and may have been inhaled and could have impacted his health and his Champagne and Aishihik First Nations (CAFN) contemporaries.